An audit on usage of fresh frozen plasma in a tertiary care hospital in north western part of India - Yadav, Anshika; Tiwari, Priyanka; Sheemar, Akhil K. (International Journal of Research in Medical Sciences, 2020)
Background: Every blood Component carries inherent risk of adverse transfusion reactions and transmission of transfusion transmitted disease (TTD). The adverse transfusion reactions are unpredictable and makes transfusion services puzzled, FFP being the most common one, it is therefore necessary that appropriate and rational use of FFP is done to make transfusion safer in terms of patient safety. The objective of the study was to assess the utilisation of FFP in a tertiary care Hospital. Methods: We conducted a retrospective study on 256 patient who received FFP transfusion at our tertiary care hospital over a period of 6 months .The usage was classified as appropriate or inappropriate based on the guidelines for FFP usage by British committee for standards in haematology, 2004 and college of American pathologist, 1994. Results: There were 256 patients in the study period who received 1370 units of FFP transfusions. The male: Female ratio was 162 M & 94 F. Most of the patients belonged to Gastroenterology Department (41.75%) followed by CTVS (15.32%). 29.48% of FFP transfusions were reclassified as inappropriate either due to Lack of indication or inappropriate doses. Conclusions: The study emphasize on the need to incurate rational use of blood components which is FFP in present case for evolving safe transfusion practices in the country. This study highlights no adherence to guidelines among clinicians which is mainly due to lack of knowledge of appropriate usage.